Pengaruh Kepemilikan Publik, Ukuran Perusahaan, Umur Listing dan Jumlah Dewan Komisaris Independen Terhadap Ketepatan Waktu Corporate Internet Reporting Pada Perusahaan Manufaktur yang Terdaftar di BEI 2017-2021 - Okvrisha Dwita Rustoputri; Riezky Amalia; Sumiadji Sumiadji (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this research was to examine the variables that effect the timeliness of corporate internet reporting in manufacturing companies on the IDX in 2017-2021. This research used the variables of public ownership, company size, age of listing and the number of independent commissioners as the independent variables and the timeliness of corporate internet reporting as the dependent variable. This research used the method of determining the sample by purposive sampling and the final sample size obtained was 17 companies. The data collection method used secondary data which is then analyzed by logistic regression analysis. The result of this research showed that partially the number of independent comissioner variable had a significant effect on timeliness of corporate internet reporting. The variable of company size, public ownership, and age of listing had no significant effect on timeliness of corporate internet reporting. Simultaneously, the variables of public ownership, company size, age of listing and the number of independent comissioner simultaneously had no significant effect on the timeliness of corporate internet reporting. The results of this research are expect to be a reference for further research and other users of financial information in understanding the factors that effect the timeliness of corporate internet reporting.